Now You See It, Now You Don't: Why Do Real Estate Agents Withhold Available Houses from Black Customers? - Ondrich, Jan; Ross, Stephen; Yinger, John (The Review of Economics and Statistics, 2003)
Potential home buyers may initiate contact with a real estate agent by asking to see a particular advertised house. This paper asks whether an agent's response to such a request depends on the race of the buyer or on whether the house is located in an integrated neighborhood. Like previous research about the causes of housing discrimination, this paper uses data from fair housing audits, a matched-pair technique for comparing the treatment of equally qualified black and white home buyers. However, we shift the focus from differences in the treatment of paired buyers to agent decisions concerning an individual house. Using a sample of all houses seen during the 1989 national Housing Discrimination Study, we estimate a random-effect, multinomial logit model to explain a real estate agent's joint decisions concerning whether to show each house to a black auditor and to a white auditor. We find evidence that agents interpret an initial housing request as an indication of a customer's preferences, but also are more likely to withhold a house from all customers when it is in an integrated suburban neighborhood (redlining). Moreover, agents' marketing efforts increase with asking price for white, but not for black, customers; blacks are more likely than whites to see houses in suburban, integrated areas (steering); and the houses agents show are more likely to deviate from the initial request when the customer is black than when the customer is white. These three findings are consistent with the possibility that agents act upon the belief that some types of transactions are relatively unlikely for black customers (statistical discrimination).